Triboelectric plasma decomposition of CO2 at room temperature driven by mechanical energy. (October 2021) - Li, Sumin; Zhang, Bao; Gu, Guangqin; Xiang, Xiaochen; Zhang, Wenhe; Shi, Xue; Zhao, Ke; Zhu, Yifei; Guo, Junmeng; Cui, Peng; Cheng, Gang; Du, Zuliang
Abstract: CO2 conversion into high value-added chemicals and fuels has received considerable attention. However, the direct decomposition of CO2 using mechanical energy, which is an important renewable energy, remains challenging. This study realized triboelectric plasma decomposition of CO2 into CO with near 100% selectivity under normal temperature and pressure, which could be directly driven by mechanical energy. CO2 − reactive species were detected by electron paramagnetic resonance spectra, verifying the existence of electron attachment dissociation (EAD) process of CO2 with a lower dissociation barrier. Average electron energy in the triboelectric plasma was decreased by modulating the distance and the polarity; thus, EAD proportion in the CO2 decomposition was increased, and a maximum CO evaluation rate of 2.2 μmol h −1 and an energy efficiency of 5.2% from plasma to chemical energy were achieved. This work provides a promising strategy for CO2 decomposition using mechanical energy. Graphical Abstract: Mechanical energy directly drives CO2 decomposition to CO with 100% selectivity via triboelectric plasma at an energy efficiency of 1.2% under room temperature and atmospheric pressure. ga1 Highlights: Direct decomposition of CO2 into CO with near 100% selectivity was realized. The reaction was driven by mechanical energy induced triboelectric plasma. The reaction underwent through electron attachment dissociation. An energy efficiency of 1.2% was achieved.